Dynamic interaction of ships while in speed [electronic resource] - Mohd. Akhmal Yusof, 1985- (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2008